Single-Photon Detection using a Quantum-Dot-Gated Resonant RLC Circuit - Nickel, Tyler; Talhouarne, Yann; Prudhom, Andrew; Allenby, Richard; Gansen, Eric (Proceedings of the Wisconsin Space Conference, 2014)
We report on a novel detection scheme that uses semiconductor quantum dots and electrical resonance to detect single photons of light. Here, a quantum-dot, optically gated field-effect transistor (QDOGFET) is used as the resistive element of a resonant RLC (resistor-inductor-capacitor) circuit. A photon is detected when it photocharges a quantum dot, thus modifying the resistance of the QDOGFET and altering the resonance condition of the surrounding circuit. Because the circuit functions as a bandpass filter, rejecting much of the electrical noise that can obscure weak photo-induced signals, the RLC detection scheme is sensitive enough to detect individual photons of light.Â